2023
DOI: 10.1002/pds.5600
|View full text |Cite
|
Sign up to set email alerts
|

mRNA COVID‐19 vaccination early in pregnancy and the risk of spontaneous abortion in an international pregnancy registry

Abstract: Purpose: mRNA COVID-19 vaccines are used in pregnant populations whether advertently or inadvertently. However, evidence on the safety of these vaccines during pregnancy is limited. The objective of this study is to evaluate the effect of BNT162b2 (Pfizer-BioNTech) and mRNA-1273 (Moderna) vaccination during the first 20 weeks of gestation on the risk of spontaneous abortion (SAB).Methods: All pregnant women who received at least one dose of BNT162b2 or mRNA-1273 and enrolled in the COVID-19 Vaccines Internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…These included eight events of spontaneous abortion, two live newborn, one fetal death, one premature baby (with maternal pre‐existing diabetes as alternative cause), 12 and a congenital central nervous system anomaly (with alprazolam as coreported drug and potential alternative cause) 13 . Two safety reports of spontaneous abortion had alternative potential causes: maternal age > 35 years 14 and coreported drugs elasomeran and fluoxetine, respectively 15,16 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These included eight events of spontaneous abortion, two live newborn, one fetal death, one premature baby (with maternal pre‐existing diabetes as alternative cause), 12 and a congenital central nervous system anomaly (with alprazolam as coreported drug and potential alternative cause) 13 . Two safety reports of spontaneous abortion had alternative potential causes: maternal age > 35 years 14 and coreported drugs elasomeran and fluoxetine, respectively 15,16 …”
Section: Resultsmentioning
confidence: 99%
“…13 Two safety reports of spontaneous abortion had alternative potential causes: maternal age > 35 years 14 and coreported drugs elasomeran and fluoxetine, respectively. 15,16 Disproportionality analyses for spontaneous abortion Spontaneous abortion was the only pregnancy outcome reported in more than five safety reports for which disproportionality analysis could be performed. Reporting of spontaneous abortion with alirocumab evolocumab was similar to that within the full database (ROR 0.06, 95% CI 0.03-0.12).…”
Section: Pregnancy Outcomesmentioning
confidence: 99%
“…Further, misclassification of exposure by the estimated date of conception was partly mitigated by applying a validated algorithm for estimating gestational age within the first trimester of pregnancy, 13 and by the additional analyses shifting the date of conception by 2 weeks. Lastly, the current study identified a miscarriage or induced abortion as that occurring up to 19 completed weeks’ gestation, a convention used by others in the study of SARS‐CoV‐2 vaccination early in pregnancy 21 . While this same time‐point is used in Canada 22 and in major clinical reviews, 23 other jurisdictions, such as the UK, consider miscarriage as that occurring up to 23 completed weeks’ gestation 24…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the current study identified a miscarriage or induced abortion as that occurring up to 19 completed weeks' gestation, a convention used by others in the study of SARS-CoV-2 vaccination early in pregnancy. 21 While this same timepoint is used in Canada 22 and in major clinical reviews, 23 other jurisdictions, such as the UK, consider miscarriage as that occurring up to 23 completed weeks' gestation. 24…”
Section: Strengths and Limitationsmentioning
confidence: 99%